Who Manages Money in Russian Households? - ИбрагимоваДиляра Ханифовна (Journal of Economic Sociology, 2012)
Based on «Monitoring of Financial Behaviour and Trust to Financial Institutions» (HSE, 2011) the paper is devoted to budgetary management in Russian households. The research seeks answers to a number of questions which the author considers important: how financial decisions are made, how the budget is managed, what gender roles within the family are. The sampling design ensures Russian-wide representation of the adult population (over 18) by gender, age, education level and type of settlement and covers some of the RF Federal Districts. The aggregate size of the sample is 1600 people. The research findings show a diversity of Russian practices in budgetary management. However, joint/partial pool, indicating equal participation of husband and wife in budgetary management, has become a dominant system. Although the joint budgetary management does not imply that spouses are equally dominant in their household relationships. The article discusses the reasons why men and women perceive an existing budgetary management system in a different way, and reveals factors which allow attributing the households to different types of budgetary management. Key factors determining a choice of a budgetary management type include per capita income, gender, and length of marriage, wife’s level of education, and the type of budgetary management practiced by the respondents’ parents. The impact of the last factor is related to gender of the household members.